KEUNIKAN, KEARTISTIKAN, DAN KENYAMANAN INTERIOR WARUNG MAKAN LESEHAN PADA MODEL BANGUNAN RUMAH BAMBU DI WILAYAH KABUPATEN SUKOHARJO JAWA TENGAH - Moedjisoewasti, Moedjisoewasti (Institut Seni Indoensia Surakarta, 2009)
Bamboo house as a subject matter of this research will be examined in a whole sphare which is reach design interior aspecst in about its uniqueness, its artistic, and its convenience. This article is also will strives what kind of study of bamboo house applied in the interior design of restaurants especially on those previous aspects above. Because of an effective propose it will be limited to the sample population among restaurants in around Sukoharjo district, Central Java. Through this article description, I would like to expose the bamboo materials had not only useful functionally but it had been a uniqueness, artictic, and convenience for the user who stay and enjoyablein all thing related to its interior design of the bamboo, besides it can be searched all thing of the construction included in the materials entirely.Keyword : bamboo construction, interior design, uniqueness, artistic, convinience